2016
DOI: 10.1259/bjr.20160302
|View full text |Cite
|
Sign up to set email alerts
|

Short-term follow-up MRI after unplanned resection of malignant soft-tissue tumours; quantitative measurements on dynamic contrast enhanced and diffusion-weighted MR images

Abstract: . Short-term follow-up MRI after unplanned resection of malignant soft-tissue tumours; quantitative measurements on dynamic contrast enhanced and diffusion-weighted MR images. Br J Radiol 2016; 89: 20160302.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
(33 reference statements)
2
13
0
Order By: Relevance
“…Del Grande et al demonstrated the improved specificity of MRI by adding low ADC to conventional imaging features of relapse (52% to 97%) [ 111 ]. These results were confirmed by Kim et al, who reported a minimum ADC of 1.16 × 10 −3 mm 2 /s, a mean ADC of 1.38 × 10 −3 mm 2 /s, and a maximum ADC of 1.61 × 10 −3 mm 2 /s in residual STT after unplanned resection [ 112 ]. Nevertheless, authors also highlighted the lower accuracies of DWI metrics (61.7% minimum ADC, 72.8% mean ADC, 75.6% maximum ADC) compared to those of DCE-MRI parameters (89% K trans , 95.1% K ep , 90.9% iAUC) [ 112 ].…”
Section: Soft Tissue Tumorssupporting
confidence: 77%
“…Del Grande et al demonstrated the improved specificity of MRI by adding low ADC to conventional imaging features of relapse (52% to 97%) [ 111 ]. These results were confirmed by Kim et al, who reported a minimum ADC of 1.16 × 10 −3 mm 2 /s, a mean ADC of 1.38 × 10 −3 mm 2 /s, and a maximum ADC of 1.61 × 10 −3 mm 2 /s in residual STT after unplanned resection [ 112 ]. Nevertheless, authors also highlighted the lower accuracies of DWI metrics (61.7% minimum ADC, 72.8% mean ADC, 75.6% maximum ADC) compared to those of DCE-MRI parameters (89% K trans , 95.1% K ep , 90.9% iAUC) [ 112 ].…”
Section: Soft Tissue Tumorssupporting
confidence: 77%
“…DCE was performed during all MRI examinations at our institute, but quantitative analysis was performed only for the last follow-up. In agreement with previous studies of DCE, our case showed a slow, gradual enhancement on the dynamic enhancement curve (8). These features may also have been present early in the follow-up, and they could have helped in suggesting the benignity of the lesion.…”
Section: Discussionsupporting
confidence: 92%
“…Multiple recent publications have demonstrated the incremental value of DWI for distinguishing malignant soft tissue tumors from benign soft tissue tumors. Quantitative evaluation using the ADC value is the key method, although the cut-off value and diagnostic performance vary among studies (3,8). To date, only one study has specifically focused on DWI of CEH, and it reported a mean value of 1.55 × 10 -3 mm 2 /sec for CEH, which was significantly different from that of malignant soft tissue tumors (0.92 × 10 -3 mm 2 / sec) (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 However, to the best of our knowledge, only a few reports have described the value of DCE-MRI in the differential diagnosis of soft-tissue tumors. 2,[14][15][16] These few reports have primarily focused on qualitative rather than quantitative analysis of DCE-MRI; thus, the results were subjective. The purpose of this study was to evaluate the potential of the semiquantitative and quantitative DCE-MRI parameters in the differential diagnosis of soft-tissue tumors.…”
Section: Introductionmentioning
confidence: 99%